(untitled) (Revista Ciência Agronômica, 2020)
The guarantee of water supply for irrigated agriculture in the semi-arid region must necessarily involve the use of lower quality water, such as brackish water. The objective of the present work was to evaluate the tolerance to salinity of the ornamental species Catharanthus roseus, Tagetes patula and Celosia argentea, using different methods. The experiment was conducted in a randomized block, arranged in a 10 x 3 factorial scheme, corresponding to 10 saline concentrations of irrigation water (ECw 0.5; 1.0; 1.5; 2.0; 2.5; 3.0; 3.5; 4.0; 5.0 and 6.0 dS m-1) and 3 ornamental species. Four salinity tolerance assessment methods were tested, using relative values or percentages of reduction in quantitative and qualitative analyses. The different methods show the highest sensitivity to salinity of C. roseus, in the seedling production stage, compared to T. patula and C. argentea species. The methods of threshold salinity and ORN index led to similar results in terms of classification of salt tolerance, with C. roseus classified as sensitive and T. patula and C. argentea as moderately sensitive. The method of Fageria (1985) allowed good separation of the species, with tolerance limits of 1.5, 2.5 and 3.5 dS m-1, respectively for C. roseus, T. patula and C. argentea. It is obvious from the comparison with literature data that the seedling production stage is more sensitive to salt stress, and it is necessary to carry out new studies aimed at attenuating the effects of stress at this stage, through the use of management techniques.